Energy balance analysis of a tropical glacier in the Andes and identification of key meteorological variables for empirical melt estimates - Yoshihiro Asaoka; Genki Saito; Takeshi Yamazaki; Edson Ramirez; Walter W. Immerzeel (Annals of Glaciology, 2025)
This study investigated surface energy fluxes of the Huayna-Potosí Glacier in Bolivia to validate existing empirical melt estimates, including degree-day models and enhanced temperature-index models. A multilayer energy balance model of the snowpack was employed to estimate melt energy and analyze its correlation with meteorological variables. The energy balance analysis revealed that melt energy peaked in October and November, the period corresponding to the progressive development toward the core wet season. Most of the net radiation was consumed by the conductive heat flux into the snowpack or glacier ice, contributing to surface temperature increases. The remaining energy was used for melt. An analysis of diurnal variation indicated that atmospheric longwave radiation suppresses melt during the dry season while driving melt during the wet season. Variables such as specific humidity and relative humidity, which are related to atmospheric longwave radiation, emerged as primary controlling factors after solar radiation in estimating melt based on meteorological variables. This study highlights that a combination of solar radiation and specific humidity outperforms existing empirical melt models that depend exclusively on temperature or a combination of temperature and solar radiation.